Discrimination based on Education in the Labor Market for Engineers - Mantell, Edmund H. (The Review of Economics and Statistics, 1974)
CONOMISTS have begun to question the efficiency and equity of the formal educational system as an institution for accumulating capital and determining the distribution of labor income.1 This paper will focus on a particular form of labor market imperfection which is related to the trend towards ever increasing amounts of schooling for more people. The imperfection consists of employment discrimination based on formal education, henceforth called screening. Screening is defined formally in the following way.2